Effect of corneal biomechanical properties on surgically-induced astigmatism and higher-order aberrations after cataract surgery - Koç,Mustafa (2016)
ABSTRACT Purpose: To investigate the relationship between biomechanical properties of the cornea and postoperative refractive changes in patients with low-level astigmatism after cataract surgery. Methods: This prospective study recruited patients undergoing cataract surgery involving 2.8-mm superior incisions. Biomechanical properties of the cornea were evaluated preoperatively using the Ocular Response Analyzer, and corneal profiles were evaluated using a Scheimpflug system (Pentacam HR). Topographic astigmatism, total corneal aberrations (TCA) and higher-order corneal aberrations (HOCA) analyses were performed preoperatively and during 1- and 3-month postoperative exams. The incidences of surgically-induced astigmatism (SIA) and HOCAs were calculated using vector analyses. Associations of the preoperative biomechanical properties of the cornea with SIA and HOCAs were evaluated. Results: This study included 28 eyes of 28 patients. The preoperative corneal hysteresis (CH) was 8.68 ± 1.86 mmHg, and the corneal resistance factor (CRF) was 8.66 ± 1.61 mmHg. At the 1-month postoperative evaluation, significant changes were observed in HOCAs (p=0.023), TCAs (p=0.05), astigmatism (p=0.02), and trefoil (p=0.033); in contrast, differences in coma (p=0.386) and spherical aberration (SA) were not significant (p=0.947). At the 3-month visit, significant changes were only observed in TCAs (p=0.02) and HOCAs (p=0.012). No relationships between the preoperative corneal hysteresis and corneal resistance factor and postoperative SIA and HOCA were identified, other than a positive correlation between the 3-month postoperative incidence of corneal hysteresis and spherical aberration. Conclusions: Despite the observed lack of relationships of preoperative biomechanical properties of the cornea with SIA and postoperative aberrations (except for SA), further studies involving larger patient groups are needed to explore the unexpected refractive deviations after cataract surgery.